2015
DOI: 10.1111/dme.12677
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody‐defined risk for Type 1 diabetes mellitus in a general population of schoolchildren: results of the Karlsburg Type 1 Diabetes Risk Study after 18 years

Abstract: The diabetes risk in schoolchildren with multiple autoantibodies was similar to the risk reported in other studies for genetically preselected probands; thus, a combined autoantibody-based screening could effectively identify at-risk individuals from the general population for future intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 29 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…A female predominance in GADA prevalence remains controversial [ 18 , 24 ]. Many studies reported GADA was more frequent in females [ 18 , 22 , 25 , 26 ], but other studies found no sex difference [ 19 , 24 , 27 29 ]. The female predilection to autoimmunity has been observed in many autoimmune diseases [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A female predominance in GADA prevalence remains controversial [ 18 , 24 ]. Many studies reported GADA was more frequent in females [ 18 , 22 , 25 , 26 ], but other studies found no sex difference [ 19 , 24 , 27 29 ]. The female predilection to autoimmunity has been observed in many autoimmune diseases [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of T1D patients there was no difference in number by sex, however, GADA prevalence was more [18,24]. Many studies reported GADA was more frequent in females [18,22,25,26], but other studies found no sex difference [19,24,[27][28][29]. The female predilection to autoimmunity has been observed in many autoimmune diseases [30,31].…”
Section: Differences In Gada Prevalence Between Male and Female Patientsmentioning
confidence: 69%
“…It is unknown whether IAA in type 1 DM patients are essential for disease pathogenesis or whether their appearance represents a major step in disease development, and this topic remains controversial in the extant literature ( 15 , 16 ). In addition, the presence of autoantibodies could indicate a non-specific, bystander autoimmune response ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of autoantibodies in type 1 DM has been well documented ( 10 , 11 , 12 , 13 , 14 , 15 , 16 ). In this disease, autoantibodies develop against a variety of antigens, including insulin (IAA) and GAD (GAD autoantibodies), all of which are localized to beta cells in the pancreas.…”
Section: Discussionmentioning
confidence: 99%